Performance of first crop of lambs/kids (Melka Werer Research Station) - Galal, E.S.E.; Gebre-Leul, S.; Feleke, G. (1977)
This report describes the results from the lambing/kidding season of October/November 1976. A total of 219 lambs were born out of which 213 and 204 survived to weaning (at the age of 3 months) and to 6 months of age, respectively. Conception rate was 90% among the ewes with a lamb percentage of 103. A least squares analysis showed that the mean of birth, 3-month and 6-month weights and daily growth rate from 3 to 6 months of age was 2.4, 11,9, 16.8 and .064 kg. Male lambs outweighed (P<.0l) females in all traits and singles were heavier (P<.0l) than twins at all stages. Singles and twins did not differ from each other in their postweaning performance. Age of dam had no significant effect on lamb performance. An attempt to estimate genetic and phenotypic parameters by half-sib analysis indicated a moderate heritability for the 6-month weight and generally low for the rest of the traits. Genetic correlations were generally unrealistic while phenotypic correlations ranged from zero between postweaning daily gain and birth weight to 0.73 between weaning and 6-month weight. Number of kids born was 26 (18 Adals and 8 Saanen x Adal) with 21 and 20 surviving to weaning (3 months) and 6 months, respectively. Kid percentage was 124. Mean of different traits was 2.34 kg for birth weight, 10.2 for weaning weight, 15.3 for 6-month weight and 0.050 kg for daily growth rate from 3 to 6 months of age. Males and crossbreds outperformed females and purebreds, respectively, in all traits. Means of different classes were reported.